PENINGKATAN KUALITAS, PROMOSI DAN DIVERSIFIKASI PEMASARAN PRODUKSI ALAT MUSIK SASANDO TRADISIONAL DAN ELEKTRIK SEBAGAI UPAYA MELESTARIKAN BUDAYA LOKAL NUSA TENGGARA TIMUR - Muntasir, Muntasir; Jutomo, Lewi; Warsito, Ali; Djati, Hyronymus; Ismail, Eddy H.; Edon, Caro David Hadel (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2019)
This activity promotes the development of traditional Sasando and Sasando electric production and design as an effort to maintain and preserve local culture with a research approach and community service in the electric edon sasando partner industry in kupang. The partner industry experienced a variety of problems, especially in the production process, procurement of raw materials, facilities and facilities for production, marketing and promotion while the demand for electric Sasando musical instruments was in great demand of the Local Market, National and International. In Production still use simple and limited equipment so that the product is finally a little. The methods used in this program are the stages of preparing work plans, implementing programs, determining performance indicators, implementing monitoring and evaluation and mentoring and preparing the final program report. The results of this service program resulted in a tranducer component, Spul Sasando Tester with high accuracy and precision so that the products and modern designs of traditional Sasando instruments and electric Sasando have high efficiency in assembly. The results of this program traditional electric Sasando and products increased from 1 product to 5-10 traditional and electric Sasando products. The promotion is carried out in the form of participating in product exhibitions, as performers in various local, national and international events. Marketing is in the form of establishing Sasando art studios, through the internet and opening outlets. The collaboration program of Nusa Cendana University, Edon Sasando Electric's regional government and partner industries is very useful to increase production and product quality based on research results that are beneficial to the wider community so that it is recommended for further research and community service.